Efektivitas Bonus Insentif, Asuransi Kesehatan, dan Hak Cuti terhadap Kesejahteraan Karyawan di PT. KAI DAOP IV Semarang - Firnanda, Muhammad Alul; Suryakencana Wibowo, Mochammad Eric; Awanis Linati Haziroh; Hertiana Ikasari (IPM2KPE, 2025)
This study aims to analyze the effect of incentive bonuses, health insurance, and leave entitlements on employee well-being at PT Kereta Api Indonesia DAOP IV Semarang. The research method used a quantitative approach, distributing questionnaires to 100 respondents using quota sampling. The data were then analyzed through validity, reliability, normality, multicollinearity, heteroscedasticity, multiple linear regression, F-test, and t-test. The results showed that incentive bonuses and leave entitlements had a positive and significant effect on employee well-being, while health insurance had a positive but insignificant effect. The conclusion of this study is that company policies emphasizing the provision of incentive bonuses and adequate leave entitlements have been proven to improve employee well-being, while health insurance has not had a significant impact. Keywords: Incentive Bonus, Health Insurance, Leave Entitlements, Employee Welfare